MINIMALLY INVASIVE INTERVENTIONS IN THE SURGICAL TREATMENT OF CHRONIC LOWER LIMB VENOUS INSUFFICIENCY - Zafarjon Bobojonovich Kurbaniyazov; Farrukh KaramatovichSayinaev; Zainiddin Yakhshiboevich Saydullaev; Feruz Asatullaevich Daminov (Scholar Express Journals, 2022)
Despite significant progress in the treatment of varicose vein disease (VVD) and the resulting chronic venous insufficiency (CVI), the diagnosis and treatment of this disease remain pressing medical and social problems. This is due to the high prevalence of the pathology, frequent relapses, the presence of complicated forms of the disease, leading to long-term disability. The main purpose of VVLL and CVN treatment is to reduce or eliminate dynamic venous hypertension, which is achieved by application of surgical and conservative methods. Surgical method is considered to be a radical one. Its success largely depends on a correct assessment of the mechanisms of phlebogemodynamic disturbances. A characteristic tendency of the development of modern phlebosurgery is the introduction of less traumatic and cosmetic methods of surgical interventions, and also the perfection of the already existing ones. This tendency aims not only to increase effectiveness, but also to achieve safety and cosmetic effect of the intervention. Endoscopic subfascial dissection of the perforating veins (ESDPV) and miniphlebectomy are methods that reduce surgical trauma and improve the aesthetic outcome of the intervention.
Keywords: crossectomy; sclerotherapy; intervention